China's linkages and leverages in Central and Eastern Europe: A new challenge for EU - Bogdan Lucian Cumpănașu (CES Working Papers, 2019)
Relying on the linkage and leverage theory, the paper aims at reviewing critical issues related to China's economic, cultural and political expansion in EU's Central and Eastern member states. Through the "17+1" format and "One Belt, One Road" initiative, China became an assertive competitor in Europe, acting on a "divide et impera" strategy through bilateral or multilateral negotiations, undermining the EU's cohesion. Also, the European Union is facing a movement of illiberal, nationalist or populist policies that occurred in the former Warsaw Pact countries which are trying to avoid Brussels' norms and therefore they are opened to other alternatives. In order to find out a pattern or relevant arguments for advancing a set of competing hypotheses or scenarios, a structured analytical technique will be applied, respectively "indicators or signposts of change", for the following countries: Bulgaria, Czech Republic, Hungary, Poland, Romania and Slovakia. In this regard, the key indicators will refer to: economic factors, the strength of the civil society, the force of the opposition or of pro-European parties and the degree of Europeanization in the analysed states. Thereby, the article will advance three important questions: 1) Is EU in competition with China and how the confrontation takes place? 2) Which are the EU's countries more likely to strengthen the partnership with China? 3) Which are the EU's own linkages and leverages in its Eastern part and how they can be used for stopping China's advancement? The results will strengthen the idea that China became a real competitive actor, trying to expand in Europe, where the peripheral ex-communist states have been placed in the core of the confrontation. Also, the article will demonstrate that EU facing a real economic rival has the capabilities to stand up and therefore act as an international power.
Keywords: 330; European Union; Central and Eastern Europe; China; leverage; linkage; competition